NARRATIVE FOR TERRORISM AND TRANSNATIONALISM ISISTHEOLOGY THROUGH THE DOCTRINE OF RELIGION - Zuhdi, Muhammad Luthfi; Hayatullah, Imam Khomaeni (UI Scholars Hub, 2020)
Acts of terrorism seem to never run out of Indonesia, from independence to the present day. Including the ideals of the establishment of an